Study the Application of Digital Currency in Sports Business - Sherin Y. Elmahdy; Ezzeldin R. Aly (European Scientific Journal, ESJ, 2026)
If Bitcoin reaches the $1 million price target by 2030, a $100 investment would grow to $6,070, representing an impressive gain of 5,970%. The investment would yield an average annual return of 746.3% if the target is met (Benzinga, 2022). According to the latest report published by Kings Research, the global sports trading cards market was valued at USD 9.69 billion in 2022 and is projected to reach USD 20.48 billion by 2030, growing at a compound annual growth rate (CAGR) of 9.01% from 2023 to 2030. One key development driving this growth is the widespread acceptance of Bitcoin as a payment method for online sports trading card purchases. The increasing use of Bitcoin and other digital currencies as legal forms of payment is fueling market expansion (Newswire US, 2023). This study introduces digital currency, focusing on one of the digital currencies, Bitcoin, which is noteworthy for being the first cryptocurrency created as a form of e-gold.  Unlike e-gold, Bitcoin is not backed by physical gold; its value is determined within the spot market. Bitcoin achieved significant success and created numerous millionaires, particularly during its peak in 2013 and 2014 (Silver, 2016). Ed Craven and Bijan Tehrani, the founders of Stake.com, built the world’s largest offshore crypto casino, generating $2.6 billion in revenue last year. Despite facing challenges due to the controversial nature of their business, they have become self-made billionaires, each worth an estimated $1.3 billion. They have used their fortunes to sponsor sports and teams (Graig, 2024). The study examines the importance of the stock market in relation to sports legislation and explores the current and future applications of digital currency within the sports business. This recent descriptive study utilized a literature review and data research analysis from various sources, including data, statistics, sports, academic articles, magazines, and editorials, to assess the impact of digital currency, particularly Bitcoin, on the rapidly growing global sports industry. The findings indicate that Bitcoin and other digital currencies have experienced significant increases in value over the past five years. Moreover, integrating digital currencies into sports business transactions could provide substantial financial benefits.